How common are ongoing problems after a hypertensive pregnancy? - Green, A; Loughna, P; Pipkin, F Broughton (Archives of disease in childhood. Fetal and neonatal edition, 2011)
Background New onset hypertension in pregnancy affects up to 6–8% of all pregnancies. For most women, hypertension and proteinuria settles following delivery. However studies have shown that blood pressure and urinalysis are often not checked in the postpartum period.1 The new National Institute for Health and Clinical Excellence (NICE) Hypertension in pregnancy guidelines suggests that this group of patients are reviewed by a medical professional postnatally. Method We set up a clinic at Nottingham City Hospital to review women after a hypertensive pregnancy (gestational hypertension (GH) and pre-eclampsia (PE) defined by ISSHP criteria).2 Women are offered an appointment at 6 weeks after delivery. Results Over a 12 month period 108 women with PE and 65 with GH have been seen. 12% of patients did not attend their appointment. 35% of women with both PE and GH were still talking antihypertensive agents at follow-up. Eight women still required more than one antihypertensive treatment. Eight women with PE (7.8%) had ongoing proteinuria (PCR >30). 22 patients (12%) required investigation for ongoing problems. Conclusions Our results support the advice from NICE that it is vital that this group of women are reviewed postnatally to ensure that ongoing hypertension and or proteinuria can be assessed, allowing investigation and diagnosis before any future pregnancies and possibly the prevention of future disease.